The estimation of economy and consumption forecast of natural gas in housing sector - Ageeva T.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2005)
The results of the estimation of natural gas saving at the expense of introduction arrangements of saving gas and replacement of its use by the electric power, and also forecast to the gas consumption in housing sector for the period up to 2030 are presented.